Ciclos de muda y características cualitativas para determinar edad de Ramphocelus carbo Pallas, 1764 (aves: Thraupidae) en la facultad de ciencias biológicas. Loreto, Perú - Saravia Llaja, Keyko Geraldy (2023)
From June 2019 to March 2020, assessments were carried out one day a month on the campus of the Facultad de Ciencias Biológicas - UNAP with the objective of characterizing the molt and plumage cycles, determining the relationship between the level of ossification and iris color with respect to age in Ramphocelus carbo, 12 mist nets were used to capture the birds and the age of the individuals was determined using the WRP classification system. The results determined that R. carbo presents a complex alternating strategy, with a complete pre-formation molt, a pre-alternate molt of partial extension and a definitive pre-basic molt of complete extension. Regarding the ossification of the skull and the age categories of the captured individuals, a significant difference was found. Iris coloration showed a change in coloration in the different age categories, from light brown in juvenile plumage individuals to dark brown with reddish tones in non-juvenile plumage individuals, no significant difference was found with respect to age.